A3 COLORECTAL CANCER DEATHS WHILE AWAITING GASTROENTEROLOGY CONSULTATION AT A CANADIAN ACADEMIC CENTRE. (1st March 2018) - Motomura, D; Kulai, T; Williams, S
Abstract: Background: Delays in access to gastrointestinal (GI) services have long been a concern of practicing gastroenterologists. Triage criteria used at the Queen Elizabeth II Health Sciences Centre (QEII HSC) in Halifax, Nova Scotia, are based on 2006 Canadian Association of Gastroenterology consensus recommendations. The demand for GI services at our academic centre has exceeded available resources and only urgent referrals are being seen within recommended timeframes. Non-urgent referrals are not being seen. Achieving nationally recommended targets for wait times remains a challenge and this raises concern for potential patient morbidity and mortality while awaiting assessment. To our knowledge, no previous studies have documented details surrounding death while awaiting GI consultation. Aims: (1) Outline patient demographics and circumstances of death while awaiting GI consultation at the QEII HSC, (2) describe referrals received on these patients and (3) determine whether cause of death was related to reason for referral. Methods: The Practice Affairs Committee at the QEII HSC is notified when a patient has died while on the GI waitlist. Basic demographic and referral information were collected on each case in addition to details surrounding the cause of death. Two gastroenterologists who are blinded to data collection reviewed original referrals and determined if the referral was triaged appropriately and whether cause of death is related, possibly related or unrelated to reason for referral. In case of disagreement between two physicians in the review process, a third independent physician provided opinion. Results: From March 2015 to September 2017, 39 deaths occurred on the GI waitlist. Mean age was 70.3 years. The majority of referrals (61.5%) came from family physicians and most (92.3%) were felt to be appropriately triaged. The average interval time from referral to death was 348 days (range 4 - 1050 days). In each triage category, patients waited significantly longer than guideline-proposed wait times. Of the 38 known causes of death, seven (18.4%) cases were directly related to referral diagnosis, while three (7.9%) cases were deemed possibly related. The most common cause of related death was colorectal cancer (n=6, 85.7%), and the most common reason for referral for these patients was anemia (n=4, 57.1%). Inappropriate triaging occurred in one of the seven related cases due to systems error. Conclusions: Significant patient mortality on GI waitlist is due to the primary GI reason for referral. As wait times for GI consultations remain well above national recommendations, this review highlights the need for additional resource allocation towards addressing the growing problem of GI wait times in Nova Scotia. Funding Agencies: None